Циркулярні бізнес-моделі в Україні - Руда, М. В.; Мирка, Я. В.; Ruda, M. V.; Myrka, Ya. V. (Видавництво Львівської політехніки, 2020)
Викладено результати дослідження у сфері циркулярної економіки та переваг упровадження цієї концепції в Україні на основі досвіду Європейського Союзу, наведено рекомендації Фонду Еллен МакАртур та Європейської комісії, що повинні взяти до уваги уряди країн з огляду на критичну екологічну ситуацію у світі. Обґрунтовано можливості формування і розвитку циркулярних бізнес-моделей в Україні на прикладі найкращих європейських практик у сфері управління відходами.

The paper presents the results of a circular economy study and the benefit of implementing this concept in Ukraine, based on the experience of the European Union, and provides recommendations from the Ellen MacArthur Foundation and the European Commission, which should be taken into account by governments in view of the critical environmental situation in the world. Possibilities of formation and development of circular business models in Ukraine on the example of the best European practices in the field of waste management are substantiated. The authors argue the following: if we go beyond the traditional (linear) industrial “Take-MakeWaste” model, the introduction of circular business models will help reduce waste, and thus minimize costs and redefine sustainable growth, focusing on positive benefits for society. It has been identified that the circular economy is a new economic model that focuses on the reuse of materials (including waste), as well as on value creation through services and intelligent solutions. The global challenges of improving waste management efficiency provide significant business opportunities. As a result, the circular system makes it possible to move materials, energy, labor and information efficiently to restore natural and social capital. This is why the circular economy is part of an effort to boost economic development, overcome wasteful consumption, and reduce undemocratic power structures in the global economy. The conducted researches have allowed establishing, that innovative business models of circular economy arise and develop first of all in the urbanized and environmentally responsible environment and are directed on reduction of dependence on material resources, increase of efficiency and increase of profit. A study of European experience in the circular economy through practical examples of five business models (circular deliveries, resource recovery, sharing platforms, product lifecycle extension, product as a service) demonstrates that: from implementation circular economies benefit both companies and consumers, as well as the community (society); in addition to short-term financial benefits, companies have long-term strategic advantages, including optimization of material flows, entry into new markets; expanding customer service or after sales service, and generating additional revenue in the provision of closed-loop services. Scaling up the circular economy is impossible without a systematic integrated restructuring, ranging from legislative regulation, technology implementation, financing and forms of doing business, to shaping society as a whole to change its habits toward the widespread use of circular products and creating new platforms and schemes for the interaction between producers and consumers of circular goods.
Circular business models in Ukraine
Keywords: сталий розвиток; відповідальне виробництво; відповідальне споживання; циркулярна економіка; циркулярна бізнес-модель; управління відходами; досвід ЄС; sustainable development; responsible production; responsible consumption; circular economy; circular business model; waste management; EU experience; 330.3